DSAC* visual re-localization [data] - Brachmann, Eric (Universität, 2020)
Supplementary training data for visual camera re-localization, particularly rendered depth maps to be used in combination with the MSR 7Scenes dataset, and the Stanford 12Scenes dataset, as well as precomputed camera coordinate files for both aforementioned datasets. For more information, also see the code documentation: https://github.com/vislearn/dsacstar
Production date: 2020-08-24
Gesehen am 14.09.2020
Keywords: Forschungsdaten; Datenbank